1-Bromoethene-1-sulfonyl fluoride (BESF) is another good connective hub for SuFEx click chemistry. Issue 47 (25th May 2018) - Smedley, Christopher J.; Giel, Marie-Claire; Molino, Andrew; Barrow, Andrew S.; Wilson, David J. D.; Moses, John E.
Abstract : 1, 2-Dibromoethane-1-sulfonyl fluoride (DESF ): a bench stable and readily accessible precursor toBESF for the synthesis of β-sultams, sulfonyl fluoride substituted isoxazoles, triazoles and Michael adducts with SuFEx-able pendant sulfonyl fluoride handles. Abstract : We demonstrate 1, 2-dibromoethane-1-sulfonyl fluoride (DESF) as a bench-stable and readily accessible precursor to the robust SuFEx connector, 1-bromoethene-1-sulfonyl fluoride (BESF ). The in situ generation ofBESF from DESF opens up several new reaction profiles, including application in the syntheses of unprecedented 3-substituted isoxazole-5-sulfonyl fluorides, 1-substituted-1 H -1, 2, 3-triazole-4-sulfonyl fluorides, 2-amino-1-bromoethane-1-sulfonyl fluorides and 4-bromo-β-sultams in good to excellent yields. These new modules comprise a pendant sulfonyl fluoride handle, which further undergoes facile and selective SuFEx reactions with a selection of aryl silyl ethers to generate stable and useful sulfonate connections.